Association of walkability and fine particulate matter with chronic obstructive pulmonary disease: A cohort study in China - Wu, Yonghao; Shen, Peng; Yang, Zongming; Yu, Luhua; Zhu, Zhanghang; Li, Tiezheng; Xu, Lisha; Luo, Dan; Yao, Xuecheng; Zhang, Xinhan; Meng, Lin; Lin, Hongbo; et al. (The Science of the total environment, 2023)
Walkability has been considered to be associated with metabolic and cardiovascular diseases, but the relationship between walkability and chronic obstructive pulmonary disease (COPD) remains unclear. Moreover, fine particulate matter (PM2.5), possibly positively correlated to walkability, may lead to an increased risk of COPD. The separate and joint effects of PM2.5 and walkability on risk of COPD were explored in our study. We used prospective data of 29,572 participants from the Yinzhou cohort in Ningbo, China. COPD cases were diagnosed based on the Yinzhou Health Information System (YHIS). Walkability was measured using walk score in relation to the built environment based on geographic information systems (GIS). Air pollution levels were assessed by fitting land use regression (LUR) models. Cox proportional hazards models were used to evaluate the relationships of PM2.5 and walkability with COPD. Furthermore, we also examined additive and multiplicative interactions between walkability and PM2.5. Overall, a total of 29,572 participants were included in the final analysis and 722 COPD incident cases were identified during 134,846 person-years of follow-up. Compared with subjects with lower walkability, individuals with higher walkability had a decreased risk of COPD (HR = 0.88, 95 % CI: 0.82–0.95) for every IQR increase. By contrast, exposure to PM2.5 (every IQR increase) was associated with an elevated risk of COPD (HR = 1.21, 95 % CI: 1.06–1.37). No interaction between PM2.5 and walkability was observed. Living in a highly walkable neighborhood could decrease risk of COPD, whereas high levels of PM2.5 were positively associated with COPD. In addition, the beneficial effects of walkability were not attenuated by exposure to PM2.5. [Display omitted] •High level of walkability was inversely associated with risk of COPD.•Long-term exposure to PM2.5 was positively associated with risk of COPD.•Protective effects of walkability were not attenuated by exposure to PM2.5 in the environment.